Pengaruh Penggunaan Pembayaran Non Tunai (Cashless Operations) terhadap Gaya Hidup Konsumtif Masyarakat pada Produk Halal di Kota Praya - Fatmawati, Fatmawati (Jurnal el-Huda, 2024)
This study aims to find the Influence of the Use of Non-Cash Payments (Cashless Operations) on the Consumptive Lifestyle of the community on halal products in Praya City partially and how much influence it has. This type of research uses quantitative research with an associative research approach and uses a questionnaire distribution that aims to determine the causal relationship between the independent variable and the dependent variable. In this study using validity and reliability and using data analysis techniques, namely classical assumption tests, simple linear regression analysis, hypothesis testing and determinant coefficients with the help of SPSS 16. The population in this study is the community in Praya City. Then to calculate the sample in this study was carried out using the Lameshow formula, and the results of the sample were 100 respondents. The results of this test showed that the use of non-cash payments had no effect on the consumptive lifestyle in Praya City. The statistical results of the t-test on the variable of the use of non-cash payments obtained a t-count value of 1.620 with a significance level of 0.109, the t-table value (df = n-2, 100-2 = 98), then the t-table value seen in the t-table is 1.984 (1.620 <1.984), then H0 is accepted Ha is rejected, meaning that the use of non-cash payments does not affect the consumer lifestyle in Praya City. Based on the results of the t-test calculation using SPSS version 16, it can be seen that the use of non-cash payments does not have a significant effect. This can be seen from the significance value of t <0.05 (0.000 <0.05) and (Tcount (1.620) <Ttable (1.984), then it is said that Ha is rejected Ho is accepted. So it can be concluded that there is no significant effect of the use of non-cash payments (cashless operations) on the consumer lifestyle in Praya City.